Les juifs à Smyrne : de l’enfermement à l’ouverture vers le monde - Henri Nahum (Revue des Mondes Musulmans et de la Méditerranée)
Set up later than those of the other cities of the Ottoman Empire, the Jewish community of Smyrna enjoyed a time of prosperity in the 17th century connected to the expanding commercial activity of the city. First located by the seaside, the Jewish quarter moved later to the center of the city, near the Konak. In the 19th century, it looked shabby; its inhabitants seldom went out of it. About 1900, the Jews of Smyrna take part in the economical expansion of the great Aegean port and give up their isolation. The fire of September 1922 which puts an end to the Greek-Turkish war changes drastically the equilibrium of the city. The transformation of the plurinational Ottoman Empire into a Turkish nation-state, the awkwardness of the republican government, a capital levy on non-Muslim citizens, the creation of the State of Israel, empty the city of its Jewish inhabitants. Today, their number is less than 2 000.